2008
DOI: 10.1103/physrevlett.100.116601
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Mobility Limit for Anisotropic Electron Transport inAlq3

Abstract: Muon spin relaxation has been used to probe the charge carrier motion in the molecular conductor Alq3 (tris[8-hydroxy-quinoline] aluminum). At 290 K, the magnetic field dependence of the muon spin relaxation corresponds to that expected for highly anisotropic intermolecular electron hopping. Intermolecular mobility in the fast hopping direction has been found to be 0.23+/-0.03 cm2 V-1 s(-1) in the absence of an electric- field gradient, increasing to 0.32+/-0.06 cm2 V-1 s(-1) in an electric field gradient of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…The calculated mobility is more than one order of magnitude greater than the highest reported for Alq3 (1 cm 2 V -1 s -1 ). 48 If we consider a more realistic figure for mobility of electrons in Alq3 (10 -6 cm 2 V -1 s -1 ), 49 the coherent transport picture is untenable even in the case that the thickness of the organic layer were very small in some areas(but still sufficiently thick to prevent direct tunneling across Alq3, i.e. thicker than a few monolayers).…”
Section: Resultsmentioning
confidence: 99%
“…The calculated mobility is more than one order of magnitude greater than the highest reported for Alq3 (1 cm 2 V -1 s -1 ). 48 If we consider a more realistic figure for mobility of electrons in Alq3 (10 -6 cm 2 V -1 s -1 ), 49 the coherent transport picture is untenable even in the case that the thickness of the organic layer were very small in some areas(but still sufficiently thick to prevent direct tunneling across Alq3, i.e. thicker than a few monolayers).…”
Section: Resultsmentioning
confidence: 99%
“…We thank the EPSRC National Mass Spectrometry Service Centre, Swansea for the analysis of Alq 3 -d 18 . This work was conducted with financial support from the Leverhulme Trust (AJD).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Spin-orbit (SO) coupling could also a possibility but this is typically weak for the light elements found in organic semiconductors [18]. In our previous work, we found that changing the atomic mass of the central ion in the quinolate system from aluminium to indium has virtually no effect on the change in efficiency with applied magnetic field [17].…”
mentioning
confidence: 99%
“…However, spin phenomena in these materials are not yet fully understood, partly due to the lack of suitable characterisation techniques, since those extensively used to characterise inorganic semiconductors are not always applicable to organic materials [1][2][3]. Muon spin relaxation (mSR) has been proven to be an applicable probe in this field, as it is sensitive to spin dynamics in organic semiconductors on a molecular length scale [4][5][6][7]. In organic semiconductors the implanted muons form a hydrogen-like system, called muonium, by capturing an electron.…”
Section: Introductionmentioning
confidence: 99%